Land disputes on legal certainty in South Sulawesi South Sulawesi in 2023 - zaenal, Abdil rahman; Sumarna, M.Ibnu (Manunggal Halim Jaya, 2024)
Objective To begin with, the plaintiff is questioned about the contents of his claim. The judge can make a decision with the help of local examination. When it comes to the construction of evidence in civil cases, the duties and responsibilities of local examination of the object of land dispute is an issue that arises. shows that local examination based on Article 153 HIR, Article 180 R. Bg or Article 211 Rv as well as SEMA No. 7 of 2001 does not reflect legal certainty because it does not regulate the mechanism of local examination in the field thoroughly, which leads to many interpretations. In addition, it is still ambiguous whether local examination is a means of evidence whose value is left to the judge or whether local examination is only an examination tool or method of obtaining evidence. Research Results and Discussion Local inspection results are a valid source of evidence in civil cases, local examinations have the following legal consequences: (1) court costs if the judge requests a local examination; and (2) the evidentiary power of the local examination. Both of these are legal consequences that need to be clarified in future regulations. elements that need to be clarified in future regulations. Conclusion In civil cases, all cases relating to immovable property are required to ensure legal certainty in the future regulation of local inspection of land. to create legal certainty regarding local inspection, the diversity of this regulation is very important. In order to create legal certainty regarding local examination, diversity of regulation is essential. Regulations regarding local examination should be established at the level of a law so that they have strong legal force against all parties involved in the case, including judges, clerks, and all other parties.